2016
DOI: 10.21834/e-bpj.v1i3.357
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Textured Surfaces of Cosmetic Packaging on Consumers' Feelings

Abstract: This study investigated what consumers' feelings were evoked when they touched different textured surfaces of 20 compact powder cases. Without seeing them, fifty respondents with and without an art-and-design-based background were asked to describe their feelings in their words as they touched the cases as well as explain them by provided words. The results show that different surface textures did evoke different respondents' feelings of which those familiar with the design were able to express a wider range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The sample group were students at the Faculties of Science and Architecture in King Mongkut's Institute of Technology Ladkrabang who were the target group of cosmetic products and whose ages were between 18 to 34 years old. The reason for choosing a group from the Faculty of Science and a group from the Faculty of Architecture was that the former group had no art-and-design-based background while the latter had it which influenced the feeling words that they uttered in a pilot study (Ritnamkam & Chavalkul, 2016). The latter group was able to respond to textures with more diverse feeling words.…”
Section: : Testing the Quality Of The 3-d Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample group were students at the Faculties of Science and Architecture in King Mongkut's Institute of Technology Ladkrabang who were the target group of cosmetic products and whose ages were between 18 to 34 years old. The reason for choosing a group from the Faculty of Science and a group from the Faculty of Architecture was that the former group had no art-and-design-based background while the latter had it which influenced the feeling words that they uttered in a pilot study (Ritnamkam & Chavalkul, 2016). The latter group was able to respond to textures with more diverse feeling words.…”
Section: : Testing the Quality Of The 3-d Modelsmentioning
confidence: 99%
“…Therefore, it has been shown that touch sensation can affect the feeling of consumers towards a product. However, this sense has not been investigated in isolation to other senses with respect to package design until the author has done a pilot study that demonstrated that touch sensation of diverse texture designs of a cosmetic package was able to convey diverse feelings (Ritnamkam & Chavalkul, 2016). For example, she found that textures with protruded patterns were able to convey the feelings of gentleness, cheerfulness, child-likeness, cuteness, and adolescent-likeness.…”
Section: Introductionmentioning
confidence: 99%